Resonant electron tunneling spectroscopy of antibonding states in a Dirac semimetal - Marques, Y. [UNESP]; Yudin, D.; Shelykh, I. A.; Seridonio, A. C. [UNESP] (American Physical Society (APS), 2018)
Recently, it was shown both theoretically and experimentally that certain three-dimensional (3D) materials have Dirac points in the Brillouin zone, thus being 3D analogs of graphene. Moreover, it was suggested that under specific conditions a pair of localized impurities placed inside a three-dimensional Dirac semimetal may lead to the formation of an unusual antibonding state. In the meantime, the effect of vibrational degrees of freedom which are present in any realistic system has avoided attention. In this work, we address the influence of phonons on characteristic features of (anti)bonding state, and discuss how these results can be tested experimentally via local probing, namely, inelastic electron tunneling spectroscopy curve obtained in STM measurements.